How urbanization influence urban land consumption intensity: Evidence from China. (June 2020) - Kuang, Bing; Lu, Xinhai; Han, Jing; Fan, Xiangyu; Zuo, Jian
Abstract: China's rapid urbanization and urban development has consumed a lot of land resources, which has attracted a great deal of both scholarly and social attention. However, the influence mechanism of urbanization on urban land consumption has not been yet fully investigated. This paper address this gap by proposing the term urban land consumption intensity (ULCI) and exploring the influence of urbanization on ULCI, based on the provincial panel data from 2000 to 2017 in China and the Panel-data Vector Autoregressive (PVAR) Model. The findings reveal that China's urbanization prompts the ULCI. However, this positive influence of urbanization on ULCI is not decisive. The change in the ULCI in China is mainly affected by its own impulse. This paper further analysis the decomposition results of urbanization, and finds that population urbanization (PU), economic urbanization (EU), spatial urbanization (SU) and social urbanization (SCU) can explain the change of ULCI in China to some extent. From the variance decomposition, EU has the largest contribution rate to the changes in ULCI, followed by SCU, SU, and PU. Policymakers should actively promote the coordinated development of different types of urbanization, and comprehensively evaluate the actual and optimal ULCI in different cities. Highlights: The influence of urbanization on urban land consumption intensity (ULCI) is explored. Panel-data Vector Autoregressive Model is adopted, based on the provincial panel data from 2000 to 2017 in mainland China. The ULCI in China is characterized by its own inertia. Population, economic, spatial and social urbanization can explain the changes of ULCI. The contribution of economic urbanization was greater than other types of urbanizations.